Perbandingan Sosiodemografi End Stage Renal Failure Yang Disebabkan oleh Diabetes Mellitus dan Hipertensi - Fitria, Najmiatul; A, Almahdy; Gillani, Syed Wasif (Jurnal Sains dan Teknologi Farmasi, 2011)
Our study aimed at evaluating sociodemographic value between diabetes mellitus and hypertension as the main cause of end-stage renal failure. Retrospective cross-sectional study was used as the research method. Two hundred end-stage renal failure patient records at 2010 were used to evaluate this study. Statistical analysis was done using statistical package of social sciences (SPSS 17Â®). Ethical clearance was issued by respective clinical research committee. Sociodemographic factors included gender, age, race, education and lifestyle. Results showed that from 200 end-stage renal failure patients there were 1% secondary to diabetes mellitus, 26.5% secondary to hypertension and 44% secondary to diabetes mellitus and hypertension. Case of end-stage renal failure in male secondary to diabetes mellitus (39%) was higher than hypertension (23.5%). End-stage renal failure secondary to diabetes mellitus was higher than hypertension (14%) in female. 33.5% patients were smokers, 22% were end-stage renal failure secondary to diabetes mellitus and the rest were secondary to hypertension. Statistical analysis showed no significant correlation (sig.>0.05) between lifestyle and end-stage renal failure secondary to diabetes mellitus and hypertension.